STUDI EKSPERIMEN PENGGUNAAN PARTICIPATORY PHOTOGRAPHY UNTUK MENINGKATKAN DETERMINASI DIRI INDIVIDU TULI - Widiastuti, Benedicta Herlina (Universitas Katolik Widya Mandala Surabaya, 2020)
Training programs for special needs individuals offered many skils but yet to answer the need of the special needs to be self-supporting. This means there are factors that can’t be answered by skills trainings, it is formulated in this study as self-determination. Self determination is the quality an individu has to direct one’s capability and actions to aim one’s purpose. This study examined the use of participatory photography to increasse self-determination. Subjects are 21 deaf students. The participants utilized camera to take pictures of their aspiration. The pictures and the stories behind are shared to the participants’ group. Exposition is held by the end of this experiment to share the pictures taken to the society. Pre test and post test are taken to measure the self-determination. Pictures analysis and personal interview are done to collect the qualitative data. Thematic analysis showed that this method laid a strong fondation for special needs individuals’ self-determination. Subjects experienced chosing, discerning, and communicating their options through pictures that they shared. Doing so, they experienced their aspirations heard and respected. These experience are factors for self-determination. T-test showed that no significance difference in self-determination. This was the effect of self-determiination deconstruction in some of the participants. It happened because the aspiration of the participants is contrary to the aspirations of their significant others.